A cAMP phosphodiesterase is essential for sclerotia formation and virulence in Sclerotinia sclerotiorum - Xu, Yan; Qiu, Yilan; Zhang, Yuelin; Li, Xin (Frontiers in Plant Science, 2023)
Sclerotinia sclerotiorum is a plant pathogenic fungus that causes white mold or stem rot diseases. It affects mostly dicotyledonous crops, resulting in significant economic losses worldwide. Sclerotia formation is a special feature of S. sclerotiorum, allowing its survival in soil for extended periods and facilitates the spread of the pathogen. However, the detailed molecular mechanisms of how sclerotia are formed and how virulence is achieved in S. sclerotiorum are not fully understood. Here, we report the identification of a mutant that cannot form sclerotia using a forward genetics approach. Next-generation sequencing of the mutant’s whole genome revealed candidate genes. Through knockout experiments, the causal gene was found to encode a cAMP phosphodiesterase (SsPDE2). From mutant phenotypic examinations, we found that SsPDE2 plays essential roles not only in sclerotia formation, but also in the regulation of oxalic acid accumulation, infection cushion functionality and virulence. Moreover, when we introduced HIGS construct targeting SsPDE2 in tobacco, largely compromised virulence was observed against S. sclerotiorum. Taken together, SsPDE2 is indispensable for key biological processes of S. sclerotiorum and can serve as a HIGS target to control stem rot in the field.